Once again on Interregional, International and Cross-age Comparison of Unemployment - Gennadi Kazakevitch (European Regional Science Association (ERSA), 2003)
Any discussion on unemployment is never restricted with the data on unemployment only. Unemployment is linked to several key indicators such as number of employed, active population and participation rate. As we often see, increase in unemployment occurs simultaneously with increase in the number of jobs, if participation rate increases at the same time. This makes doubtful any simplistic interregional, international, inter-temporal or cross-age comparison of unemployment data taken in isolation from corresponding participation rates. Interregional and international differences in unemployment depend not only on general economic situation in compared regions or countries, but also on historic and cultural differences. For example, it is inaccurate to compare unemployment situation in two countries with different participation rate of females (such as Japan and Australia). Neither regional employment situations are comparable if their economic, social, ethnic bases considerably differ from each other. Inter-temporal or time series analysis of unemployment makes sense only if participation rate is stable. By no means this is applicable to such country as Australia, where the participation rate fluctuates, depending upon a phase in the business cycle. Methodological inaccuracy of cross-age analysis is especially clear with regard to the youth unemployment measurement which excludes from consideration potentially most employable young people continuing their full-time education or professional training. An approach is suggested, which allows making the above-mentioned comparisons more accurate. An artificially constructed unemployment rate indicator is based on the actual unemployment data, actual number of full time jobs, and a participation rate assumed to be equal across compared populations. This way constructed indicator shows unemployment disparities if there were no interregional international, inter-temporal of cross-age disparities in participation rate. Proposed indicators are compared with conventional ones for several developed market economies with different cultures (Australia, USA and Japan). An analogous time series analysis is conducted on unemployment in the states and territories of Australia. In conclusion, the issue of youth unemployment in Australia is considered from the perspective of the suggested comparative measurement.
Keywords: 330